"We Are All in This Struggle Together": Toward an Active Communal Construct of Citizenship. (June 2021) - Vickery, Amanda E.
This qualitative case study explores how an African American woman social studies teacher made sense of the construct of citizenship utilizing historical and experiential knowledge. The multiple intersections of the participant's identity affected the ways in which she understood and taught citizenship to her high school students. She chose to reject the dominant notion of citizenship because it failed to align with her experiences as an African American woman and instead chose to teach an active and community-centered citizenship. This study hopes to shed light on how alternative notions of citizenship may be utilized in social studies classrooms.